BETWEEN ENGLISH, INDONESIAN, AND ARABIC LANGUAGE: INVESTIGATING CODE-SWITCHING IN ENGLISH ONLINE WRITING - Yanuar, Ivo Dinasta (SIGEH ELT : Journal of Literature and Linguistics, 2024)
This study investigates code-switching practices among undergraduate students in online English writing at Sharia Tourism department in Cirebone, Indonesia. The research explores how these students navigate code-switching between English, Arabic, and their local languages. Furthermore, this research analyzes the factors which contribute code-switching in English writing online communication among young people. The data for this research are from questionnaires and analyzed quantitatively. The result show that the use of Arabic dominates the language choice for code – switching among undergraduate students in Cirebon, Indonesia. The most factor is caused by the effort to show their identity and maintain social relationship. This research contributes for educators and policymakers in developing effective teaching methods and fostering inclusive online learning environments.